2016
DOI: 10.1097/meg.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 variant is the most common variant associated with thiopurine-induced early leukopenia and alopecia in Korean pediatric patients with Crohn’s disease

Abstract: Mutations of the NUDT15 and TPMT gene accounted for ∼88% of cases with thiopurine-induced early leukopenia. Extensive hair loss was a recognizable early symptom in patients with the homozygous NUDT15 c.415C>T variant. Sequencing of the NUDT15 genes can guide the clinicians before thiopurine medication. An alternative immunosuppressive medication is recommended for patients with homozygous NUDT15 c.415C>T variant. For those with the heterozygous variant, half the usual dose of AZA can achieve efficacy comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 10 publications
5
48
0
Order By: Relevance
“…Importantly, many investigators have been able to replicate these results in studies of thiopurine-treated patients with IBD or ALL 789101112131415161718. In the current study, we successfully established a significant association between NUDT15 p.Arg139Cys and thiopurine-induced leukopenia and severe hair loss.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Importantly, many investigators have been able to replicate these results in studies of thiopurine-treated patients with IBD or ALL 789101112131415161718. In the current study, we successfully established a significant association between NUDT15 p.Arg139Cys and thiopurine-induced leukopenia and severe hair loss.…”
Section: Discussionsupporting
confidence: 56%
“…The high specificity and sensitivity (89.4% and 93.2%, respectively) of NUDT15 p.Arg139Cys recorded by these authors indicate that this variant, rather than TPMT polymorphisms, may be an effective genetic marker for predicting thiopurine-induced adverse events, at least in East Asian populations. To date, this strong association has been confirmed in numerous studies involving subjects with IBD or ALL 789101112131415161718. In addition, a further investigation identified 4 NUDT15 coding variants, including p.Arg139Cys, that influence both nucleotide diphosphatase activity and levels of thiopurine active metabolites, and found loss-of-function NUDT15 variants to be associated with thiopurine intolerance 13.…”
Section: Introductionmentioning
confidence: 74%
“…The allele frequency for the variant T allele in this patient cohort was 7.5% (9/120). From previous studies, patients carrying one or more of the loss-of-function missense variants were found to have increased risk of developing leukopenia during thiopurine therapy [26]; thus, the eight patients (13.3%) with one or more mutant alleles were identified to have thiopurine intolerance by NUDT15 genotyping. The remaining 52 (86.7%) were homozygous for the wild-type C allele and were unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…However, thiopurine‐induced leukopenia is less associated with TPMT variants in Asian IBD patients . A genome‐wide association study of Korean patients with Crohn's disease revealed that a missense variant in exon 3 of nucleoside diphosphate‐linked moiety X‐type motif 15 ( NUDT15 ) gene (R139C; rs116855232) is associated with thiopurine‐induced leukopenia . Furthermore, Japanese studies have revealed that severe leukopenia and complete hair loss are inevitable in patients with the homozygous variant of NUDT15 R139C (T/T genotype) and demonstrated that patients harboring the heterozygous variant (C/T genotype) experience early leukopenia more frequently than those of the wild‐type genotype (C/C genotype) …”
Section: Introductionmentioning
confidence: 99%